FUNDAMENTAL UNITS AND REGULATORS OF AN INFINITE FAMILY OF CYCLIC QUARTIC FUNCTION FIELDS - Lee, Jungyun; Lee, Yoonjin (Journal of the Korean Mathematical Society, 2017)
We explicitly determine fundamental units and regulators of an infinite family of cyclic quartic function fields $L_h$ of unit rank 3 with a parameter $h$ in a polynomial ring $\F_q [t]$, where $\F_q$ is the finite field of order $q$ with characteristic not equal to $2$. This result resolves the second part of Lehmer's project for the function field case. KCI Citation Count: 0